Manufacture and working procedure of Temperature Control Unit (TCU). Issue 4 (March 2021) - Sabri, F N; Mukhidin, M; Disastra, Y S; Hasan, B
Abstract: Internet of Think (IoT) is a system that over time the development of technology makes it easy for users to carry out daily activities. Using the principle of the Internet of Think (IoT) making temperature control devices in a room can be more easily done. This room temperature controller is based on the ESP8266 microcontroller by utilizing an internet connection, users can find out the temperature in the room anywhere and anytime by utilizing the Message Queuing Telemetry Transport (MQTT) protocol. This research is intended to make it easier to supervise, control, and manage a job in this case that is for room temperature. In its application, that is bias for broiler chicken coops, server room temperature regulators, or other temperature monitoring required. Monitoring the temperature of a room in real time and not needing to be directly in place is an advantage of this research. The lowest room temperature can be adjusted as you wish or the standard we want. The output from this tool can be in the form of lights, fans, air conditioners, etc.